On the taxonomy of Barsine striata (Bremer & Grey) and Barsine pulchra (Butler) (Lepidoptera: Erebidae: Arctiinae) with descriptions of three new species from Indochina - Volynkin, Anton V.; Černý, Karel; Huang, Si-Yao; Saldaitis, Aidas (Zootaxa, 2022)
The taxonomy of Barsine striata (Bremer & Grey, 1852) and B. pulchra (Butler, 1877) is revised. Three new species are described: B. evrys sp. n. (Central and South Vietnam, and South-East Thailand), B. robusta sp. n. (North Thailand), and B. laotiana sp. n. (Сentral Laos). One taxon is revived from synonymy and upgraded to subspecies level: Barsine pulchra pulcherrima (Staudinger, 1887), stat. rev. Miltochrista gratiosa kurilensis Bryk, 1942, is excluded from the synonymy with Barsine striata and placed in synonymy with B. pulchra (=Miltochrista gratiosa kurilensis Bryk, 1942, stat. rev.). Lectotypes for Lithosia striata Bremer & Grey, 1852, Hypoprepia lanceolata Walker, 1854 and Miltochrista pulchra Butler, 1877 are designated. Adults, male and female genitalia are illustrated.